If it's not what You are looking for type in the equation solver your own equation and let us solve it.
+t+-7=-56
We move all terms to the left:
+t+-7-(-56)=0
We add all the numbers together, and all the variables
t+49=0
We move all terms containing t to the left, all other terms to the right
t=-49
| 2=-14a-8+9a | | 2k–8=12 | | -3=|4-2x^2| | | -4(x2+x+2)=0 | | 6-(d+3)+11d=83 | | 3(d+12)-7d=8-(2d+2d | | 3(4-11)+15=-6(-x+7) | | 7+10n=53 | | -7x-20=-35 | | 22+2a-a-6=37 | | 4(5c+6)=20c+20 | | 4w=w=21 | | 12x+10+10x+60=180 | | 11z+15=-5+9z | | 3(12+q)=108 | | 4m-6-7m=18 | | 1/3z=32-4/5 | | 5+x=−11 | | 3x-2=16* | | 6x-13=4x-9 | | (2x)(8)=20 | | 64=-6n+4 | | 2x-18=4x-24 | | 7x+21+10x-3=26 | | r/10=8.5 | | 2x+18+5x–6=90 | | -18+8q=11q | | 8x+5=10/3(x)-2 | | 5x−20=3x+6 | | k/6-8=0 | | -9=4x-7 | | 6x+7x=54 |